Collision tumour of large-cell neuroendocrine carcinoma and adenocarcinoma in the stomach: A case report. - Payet, Eduardo (2016)
Concurrence of adenocarcinoma and large-cell neuroendocrine carcinoma of the stomach is a rare condition. Here, we report a case of gastric collision tumour with large-cell neuroendocrine carcinoma and adenocarcinoma. A 71-year-old Peruvian man presented with nausea, epigastric pain, and weight loss for seven months. An Endoscopic evaluation revealed a huge ulcerative and infiltrative mass in the upper and middle third of the stomach. The patient underwent a D2 total gastrectomy. Microscopically, two separated and attached ulcerative lesions were recognised. The proximal to the cardial lesion showed neuroendocrine morphology and immunoreactivity for synaptophysin, and the other a moderated tubular adenocarcinoma Borrmann type III. Both lesions invaded serosa and lymph nodes metastases were found in 17 of 41 lymph nodes retrieved (one lymph node with neuroendocrine metastatic deposits).